Performance Enhancement of Gulf of El Zayt Wind Farm in Egypt Using a Novel Optimized Seconded Sliding Mode Control - Mohamed Ebeed; Nagwa Elbadry; Khairy Sayed; Ahmed Rashad; Sulaiman Z. Almutairi; Ahmed T. Hachemi; Emad A. Mohamed; Shazly A. Mohamed (IEEE Access)
Gulf of El Zayt wind farm is one of the giant projects for wind stations in Egypt, as its production is expected to reach up to 580 MW. Sliding Mode Control (SMC) is characterized by its ability to achieve rapid control of systems which suffer from the impact of uncertainty variables. This paper presents an improved method to enhance the effect of Seconded Order Sliding Mode Control (SSMC) on the applied systems. This improved method consists of a combination of the SSMC and proportional integral controller (PI) which is named as an optimized Seconded Order SMC-PI Control (OSSMC-PI). The Slime Mould Algorithm (SMA) and the particle swarm optimization (PSO) methods are applied to assign the optimal gains of proposed OSSMC-PI controller. To clear up the achievement of this improved method, its impact on the performance of Gulf of El Zayt wind farm stage one - 120 MW (GZWF-120) during a three-phase fault is compared with the impact of different control technologies such as the proportional integral controller (PI), optimized PI controller and PI-SMC controller the performance of GZWF-120. The system performance is enhanced considerably with the application of the suggested OSSMC-PI controller compared to the classical SM controller and PI controller.